2022
DOI: 10.1002/gsj.1454
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of post‐mergers and acquisitions reorganization: Integration and differentiation

Abstract: Research SummaryThis article applies a mixed‐method approach to explore the complexities of post‐mergers and acquisitions (M&A) integration processes. Extant literature provides significant insights regarding the impact of task and human integration and their influence on post‐integration processes. However, the literature often fails to differentiate between subelements of these two dimensions. This article investigates task and human integration in a cross‐border M&A aimed at efficiency and innovativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Structural integration and synergy play a critical role in a post-merger. Besides, the literature emphasizes the gap between the desired and unpleasant levels of integration and synergy in post-mergers (Bodner and Capron, 2018;DePamphilis, 2019;Garzella et al, 2017;Jeong, 2021;van Oorschot et al, 2022;Tarba et al, 2017;Teerikangas and Thanos, 2018). This study accentuates strategic fit, knowledge transfer, economic performance, integration costs, resource complementarity and performance orientations for structural integration.…”
Section: 8 2280mentioning
confidence: 88%
See 1 more Smart Citation
“…Structural integration and synergy play a critical role in a post-merger. Besides, the literature emphasizes the gap between the desired and unpleasant levels of integration and synergy in post-mergers (Bodner and Capron, 2018;DePamphilis, 2019;Garzella et al, 2017;Jeong, 2021;van Oorschot et al, 2022;Tarba et al, 2017;Teerikangas and Thanos, 2018). This study accentuates strategic fit, knowledge transfer, economic performance, integration costs, resource complementarity and performance orientations for structural integration.…”
Section: 8 2280mentioning
confidence: 88%
“…Besides, the literature emphasizes the gap between the desired and unpleasant levels of integration and synergy in post-mergers (Bodner and Capron, 2018; DePamphilis, 2019; Garzella et al. , 2017; Jeong, 2021; van Oorschot et al. , 2022; Tarba et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dzikowska et al (2023) point out that this can often be observed in the form of greater internal differentiation through the proliferation of heterogenous subsidiary units. International expansion is often done through cross‐border mergers and acquisitions, which, as shown by van Oorschot et al (2022), imply intricate post‐acquisition integration processes. Of course, MNCs develop capabilities to cope with the added challenges and explore strategies that suitably match their resources and distinct advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Internal structural complexity relates to complexities such as the interdependencies and coordination requirements between organizational tasks and activities within and across countries. In this respect, van Oorschot et al (2022) investigate the complexity of post-merger and acquisition (M&A) reorganization. Using a mixed-methods approach to a large acquisition in the shipping industry, the authors emphasize the distinction and challenge of task and human integration and propose a conceptual framework to understand post-M&A integration based on the primary source of synergy (complementary vs. similarity) and location of target and acquirer (separated vs. collocated).…”
Section: Complexity and Global Strategymentioning
confidence: 99%
See 1 more Smart Citation